Optimizing Planar and 2-Planar Parsers with MaltOptimizer - Miguel Ballesteros (Procesamiento del Lenguaje Natural, 2012)
MaltOptimizer is a tool that is capable of finding an optimal configura- tion for MaltParser models, taking into account that nowadays dependency parsers require careful tuning in order to obtain state-of-the-art results, and this tuning is normally based on specialized knowledge. The Planar and 2-Planar parsers are two different parsing algorithms included in MaltParser. In the present paper, we show how these two parsers can be included in MaltOptimizer processes comparing them with the rest of MaltParser algorithm families, and how we can define a deep feature search and selection by using MaltOptimizer for these two algorithms. The experiments show that by using MaltOptimizer we can improve parsing accuracy for Planar and 2-Planar parsers by up to 8 percent absolute (labeled attachment score) compared to default settings.